Dusun custom in Putatan District - Osman bin Orang Kaya Kaya Pangeran Haji Omar Pangeran 1884-; Woolley, G. C. (George Cathcart) 1876-1947 (Natural History Publications (Borneo), 2006)
Compilation of Dusun adat and customary laws in Putatan, Sabah.